2010
DOI: 10.1021/ml100060m
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Albumin-Binding Prodrug of Doxorubicin That Is Cleaved by Prostate-Specific Antigen

Abstract: We have developed a novel albumin-binding prodrug of doxorubicin that incorporates p-aminobenzyloxycarbonyl (PABC) as a 1,6 self-immolative spacer in addition to the heptapeptide, Arg-Ser-Ser-Tyr-Tyr-Ser-Leu, as a substrate for the prostate-specific antigen (PSA) that is overexpressed in prostate carcinoma and represents a molecular target for selectively releasing an anticancer agent from a prodrug formulation. The prodrug exhibited good water solubility and was bound rapidly to the cysteine-34 position of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…It was earlier reported that in the analysis of the cleavage products of purified semenogelin I (SgI) and II (SgII) by PSA, the amino acid Ser was found at position P1′ at a high frequency among the products. 15 Also, the dipeptide Ser-Leu has been inserted at position P1′ and P2′ in some PSA-activated prodrugs of doxorubicin 16,17 and TGX-D1. 18 The Ser-Leu linker appears to be removed in these studies by aminopeptidases present ubiquitously in the extracellular fluid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was earlier reported that in the analysis of the cleavage products of purified semenogelin I (SgI) and II (SgII) by PSA, the amino acid Ser was found at position P1′ at a high frequency among the products. 15 Also, the dipeptide Ser-Leu has been inserted at position P1′ and P2′ in some PSA-activated prodrugs of doxorubicin 16,17 and TGX-D1. 18 The Ser-Leu linker appears to be removed in these studies by aminopeptidases present ubiquitously in the extracellular fluid.…”
Section: Resultsmentioning
confidence: 99%
“…However, the enzyme responsible for the cleavage of Ser-Leu dipeptide is not specified. Elsadek et al carried out the cleavage in LNCaP tumor homogenate, 17 but the homogenate has a mixture of enzymes that can cause diverse biochemical processes. Hence, it is difficult to know which enzyme in the mixture specifically does the cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…14 This doxorubicin dipeptide was further degraded in LNCaP prostate tumor tissue homogenates and in PSA-positive LNCaP luciferase-neomycin cell lysates to release doxorubicin as a final cleavage product within few hours by adventitious proteases. 14 After cleavage and deacylation, the PABC spacer decomposes in 1,6-benzylelimination and spontaneously releases the free drug.…”
Section: Introductionmentioning
confidence: 99%
“…15 Moreover, the dipeptide H-Ser-Leu-PABC-DOXO was significantly more active against a PSA-expressing prostate cancer cell line (LNCaP lentiviral luciferaseneomycin (LLN)) than either H-Ser-Arg-DOXO, the cleavage product of PSA5, or H-Ser-Leu-DOXO that both do not contain the PABC spacer. 14 As a consequence and as a main goal of this study, we set out to investigate the antitumor efficacy of PSA9 in comparison with conventional doxorubicin in a mouse model of human prostate cancer using luciferasetransduced LNCaP cells orthotopically implanted in the prostate of severe combined immunodeficiency (SCID) mice. As the LNCaP LLN cell line used in this study was genetically altered to express luciferase, tumor growth could be followed in vivo, and bone, lung, liver and inguinal lymph nodes as the most susceptible organs for the formation of metastases in progressive prostate cancer could be analysed using an in vitro luciferase assay.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] Among these, protein-based therapeutics are a promising class of nanocarriers, which earned great interest as translational drug delivery platform with increasing numbers of clinical trials in different phases. [16] In particular, the abundant blood plasma protein human serum albumin (HSA) has been applied as drug delivery system, and albumin nanoparticles, [17] albumindrug conjugates, [18,19] albumin-binding drug derivatives, [20] albumin-coated nanoparticles, [19,21] and prodrugs [22][23][24] have been developed and advanced into clinical trials. Nanoparticle albumin-bound (Nab) formulations consist of denatured albumin aggregates that form nanoparticles with sizes of ≈100-200 nm with encapsulated lipophilic drug molecules.…”
mentioning
confidence: 99%